Graduación en el Teatro Melico Salazar. (UNED, 2016)
Invitada en el podio. Aparecen en la mesa principal María Graciela Núñez Núñez, Gisele Bolaños Mora, Luis Guillermo Carpio Malavasi - Rector, Ronald Bonilla Carvaja- Escritor, Katya Calderón Herrera y Nelson José Briceño Vargas